Hyperammonemic encephalopathy associated with 5-fluorouracil in a patient with previous orthotopic liver transplantation. Issue 2 (2nd April 2020) - Marella, Hemnishil K.; Peravali, Rahul; Jain, Amit L.; Nair, Satheesh; Maliakkal, Benedict; Agbim, Uchenna; Verma, Rajanshu
Abstract: 5-Fluorouracil (5-FU)–based chemotherapy is the most common regimen used to treat metastatic or advanced colon cancer. Neurotoxicity is a rare but serious adverse effect of 5-FU–based therapy. We report an unusual case of 5-FU–induced hyperammonemic encephalopathy in a patient with recurrent colon cancer that metastasized to the liver and lung. Two days after receiving the third dose of FOLFOX, he presented with altered mental status, agitation, abdominal pain, nausea, and vomiting. His total ammonia level was 434 μmol/L, for which he was treated with lactulose retention enema and lactulose via nasogastric tube. Over the next 24 hours, his condition improved significantly.